Direct Antibiotic Activity of Bacillibactin Broadens the Biocontrol Range of Bacillus amyloliquefaciens MBI600 - Dimopoulou, Anastasia; Theologidis, Ioannis; Benaki, Dimitra; Koukounia, Marilena; Zervakou, Amalia; Tzima, Aliki; Diallinas, George; Hatzinikolaou, Dimitris G.; Skandalis, Nicholas (mSphere, 2021)
Siderophores have mostly been studied concerning their contribution to the fitness and virulence of bacterial pathogens. In the present work, we isolated and characterized for the first time the siderophore bacillibactin from a commercial bacterial biocontrol agent. Bacillus amyloliquefaciens is considered the most successful biological control agent due to its ability to colonize the plant rhizosphere and phyllosphere where it outgrows plant pathogens by competition, antibiosis, and inducing plant defense. Its antimicrobial function is thought to depend on a diverse spectrum of secondary metabolites, including peptides, cyclic lipopeptides, and polyketides, which have been shown to target mostly fungal pathogens. In this study, we isolated and characterized the catecholate siderophore bacillibactin by B. amyloliquefaciens MBI600 under iron-limiting conditions and we further identified its potential antibiotic activity against plant pathogens. Our data show that bacillibactin production restrained in vitro and in planta growth of the nonsusceptible (to MBI600) pathogen Pseudomonas syringae pv. tomato . Notably, it was also related to increased antifungal activity of MBI600. In addition to bacillibactin biosynthesis, iron starvation led to upregulation of specific genes involved in microbial fitness and competition. IMPORTANCE Siderophores have mostly been studied concerning their contribution to the fitness and virulence of bacterial pathogens. In the present work, we isolated and characterized for the first time the siderophore bacillibactin from a commercial bacterial biocontrol agent. We proved that its presence in the culture broth has significant biocontrol activity against nonsusceptible bacterial and fungal phytopathogens. In addition, we suggest that its activity is due to a new mechanism of action, that of direct antibiosis, rather than by competition through iron scavenging. Furthermore, we showed that bacillibactin biosynthesis is coregulated with the transcription of antimicrobial metabolite synthases and fitness regulatory genes that maximize competition capability. Finally, this work highlights that the efficiency and range of existing bacterial biocontrol agents can be improved and broadened via the rational modification of the growth conditions of biocontrol organisms.